Is the visceral adiposity index a potential indicator for the risk of kidney stones? - Hou, Bingbing; Shen, Xudong; He, Qiushi; Chen, Yang; Xu, Yuexian; Chen, Mingwei; Xi, Junhua; Hao, Zongyao (Frontiers in Endocrinology, 2022)
Objective: To determine whether the visceral adiposity index (VAI) was linked to the risk of kidney stones (KS) in the representative U.S. adults. Methods: We investigated 59842 participants who joined the 2007–2018 National Health and Nutrition Examination Survey. The association between the visceral adiposity index (VAI) and KS was identified by logistic regression analysis. Meanwhile, the subgroup analysis as well as the calculation of dose‒response curves were also utilized to identify sensitive groups. Results: Data from 29384 participants were available, including 2781 self-reported ever experiencing KS diseases. Overall, the VAI was 0.74 (0.70, 0.78) in the KS group, while 0.55 (0.52, 0.57) in the control group. After adjusting for confounders, the prevalence of KS increased by 13% for each unit of VAI increment (OR = 1.13, 95% CI: 1.08, 1.19). Moreover, a linear relationship was found between the VAI and the prevalence of KS. By subgroup analysis, we found that a positive correlation between VAI and the risk of KS both in male (OR=1.14, 95%CI:1.07, 1.22) and female (OR=1.14, 95%CI:1.05, 1.24), White (OR=1.20, 95%CI:1.11, 1.28) and other race, all aged subgroups, nonhypertensive (OR=1.06, 95%CI:1.08, 1.25) and nondiabetic subgroups (OR=1.14, 95%CI:1.07, 1.21). Conclusions: Elevated VAI was strongly associated with KS in representative U.S. adults, which may be a promising indicator for the risk of kidney stones.